Arctic cinema: from horror through dramas and thrillers To Action movies and fiction (Part II) - I. S. Zonn (Проблемы постсоветского пространства, 2023)
The article examines Arctic thrillers, action films and fantasy films. Presented kaleidoscope of horror, drama, thriller, science fiction and action films, with all its plot differences, is united by almost a single location, the Arctic north. Against his background, all maginable and unimaginable events occur. It enhances or weakens the role of what is happening with its whiteness, making the viewer’s screen even whiter. This is an artistic space in which characters are placed and actions, are performed. The silence of the Arctic is its action. The films reviewed are extremely different, responding to the spirit of the time when they were filmed. Their placement about genres is conditional since they all have a cinematic hybridity. Each tape combines all kinds of genres under consideration. We tried to correlate a number of films with temporary political-social processes.